Do subtle findings on chest X-ray predict worse outcomes for paediatric asthma?. Issue 1157 (3rd December 2020) - Abeles, Michael; Akerman, Meredith; Halaby, Claudia; Pirzada, Melodi
Abstract: Background: Asthma, a common childhood condition, often presents with chronic cough. While evaluating for chronic cough, many specialists obtain a baseline chest radiograph (CR) to assess for other causes. Usually read as 'normal', sometimes CRs will reveal evidence of airway inflammation in the form of subtle findings, such as 'increased interstitial markings' or 'peribronchial thickening'. There is sparse literature in the outpatient setting correlating findings on baseline CRs with adverse outcomes such as systemic steroid use, emergency department (ED) visit or hospitalisation. Methods: This was a retrospective study of patients seen at our institution's Pediatric Pulmonology outpatient clinic. We reviewed the charts of all new patients aged 0–18 years who presented between January 2015 and December 2017. Patients were included if they were diagnosed with asthma, had a CR after the initial visit and were followed up at least twice. Adverse outcomes include systemic steroid use, ED visit or hospitalisation. Results: 130 subjects were included. 89 subjects had clear CRs and 41 subjects had CRs with airway inflammation. Overall events were higher in the airway inflammation group (22.5% vs 46.3%, respectively, p<0.0058). There were no significant differences between in terms of oral corticosteroid use or hospitalisations. There was a significant difference between the two groups in terms of ED visits (2.2% vs 14.6%, respectively, p=0.0121). Conclusion: This study shows a positive correlation between airway inflammation findings on baseline CR and subsequent ED visits in patients with asthma.